2010
DOI: 10.2174/138920010792927325
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the Human Breast Cancer Resistance Protein (BCRP/ABCG2)

Abstract: The human breast cancer resistance protein (BCRP/ABCG2) is the second member of the G subfamily of the large ATP-binding cassette (ABC) transporter superfamily. BCRP was initially discovered in multidrug resistant breast cancer cell lines where it confers resistance to chemotherapeutic agents such as mitoxantrone, topotecan and methotrexate by extruding these compounds out of the cell. BCRP is capable of transporting non-chemotherapy drugs and xenobiotiocs as well, including nitrofurantoin, prazosin, glyburide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
185
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(193 citation statements)
references
References 129 publications
(205 reference statements)
2
185
0
2
Order By: Relevance
“…Many studies have confirmed that BCRP, a new breast cancer resistance protein, belonging to a superfamily of ABC, is not only expressed in normal tissues, such as brain tissue, bile and intestinal mucosa, etc, but also in a large number of tumor tissues. The high expression of BCRP in tumor cells could specifically transport mitoxantrone, methotrexate, camptothecin and many anticancer drugs, forming the important cause of tumor cell resistance (Robey et al, 2009;Ni et al, 2010;Getz et al, 2011). Recent researched suggested that BCRP had protective effects on stem cell differentiation and development, and would have a large number expression in cancer stem cells Ding et al, 2010;Natarajan et al, 2012), which might provide the theoretical support of BCRP's potential overcoming the tumor resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have confirmed that BCRP, a new breast cancer resistance protein, belonging to a superfamily of ABC, is not only expressed in normal tissues, such as brain tissue, bile and intestinal mucosa, etc, but also in a large number of tumor tissues. The high expression of BCRP in tumor cells could specifically transport mitoxantrone, methotrexate, camptothecin and many anticancer drugs, forming the important cause of tumor cell resistance (Robey et al, 2009;Ni et al, 2010;Getz et al, 2011). Recent researched suggested that BCRP had protective effects on stem cell differentiation and development, and would have a large number expression in cancer stem cells Ding et al, 2010;Natarajan et al, 2012), which might provide the theoretical support of BCRP's potential overcoming the tumor resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Other research has suggested higher order of homo-oligomer on plasma membranes, which could also regulate ABCG2 function by dynamic association and dissociation of ABCG2 monomers [76] . Accordingly, it is currently unknown whether a homodimer or a homo-oligomer is the dominant functional unit of ABCG2 in the plasma membrane [77,78] .…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 99%
“…Clinically, high expression levels of ABCG2 have been found in many solid tumors, especially adenocarcinomas of the digestive tract, endometrium, lung and melanoma [77] . In addition, Damiani et al [79] found that ABCG2 was overexpressed in 33% of AML patients and that this feature was significantly associated with shorter diseasefree survival and higher risk of relapse.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 99%
“…In contrast to Pgp and MRP1, it contains only one NBD preceding one TMD with six membrane spanning helices (Ni et al, 2010). BCRP has been identified to have a potential impact on drug resistance in hematologic malignancies like AML and CML due to its frequent expression on malignant hematopoietic and lymphoid cells (Natarajan et al, 2012).…”
Section: Bcrp In Anticancer Drug Resistancementioning
confidence: 99%